Prototipe Robot Kapal Pengukur Tingkat PH dan Turbiditas Air Berbasis Metode Modified Fuzzy - Firman Al Rahmat; Unang Sunarya; Rohmat Tulloh (Universitas Syiah Kuala, 2018)
The quality of lake or pond water is usually determined through testing of several water samples in the laboratory. This certainly takes time especially when the place of measurement is wide enough. This research designed a water quality gauge control based on the Modified Fuzzy method and equipped with pH sensors and turbidity sensors to measure the potential of Hydrogen (pH) and turbidity of water. The Graphical User Interface (GUI) on a laptop was used to control the ship manually and display the measurement results. Wireless control through Bluetooth communication was used to set up the two DC motor as the driving force of the ship. The modified Fuzzy method was used to divide water quality into 3 categories that are good, not good, and poor. The test results proved that every command on the GUI can be run by the ship and the measurement results can be displayed directly to the user. The maximum distance measurement using Bluetooth was 28 meters. The pH sensors and turbidity sensors were able to measure at any specified location point. The pH value of lake water was measured at each point varies from 6.5 to 8, while the measured turbidity values ranged from 5 NTU (Nephelometric Turbidity Unit) to 49 NTU.